The effects of hand-eye coordination training using the circuit method on the backhand drive skill in table tennis athletes aged 8-12 years - Hary Widodo; Tomoliyus Tomoliyus; Khairil Fajri; Muh Batistuta Fitoni Nuradila (Jorpres (Jurnal Olahraga Prestasi), 2026)
The backhand drive is a basic table tennis stroke performed on the backhand side with a relatively compact swing in front of the body. This stroke requires the integration of observing the ball’s trajectory, timing the contact, adjusting the racket angle, and coordinating the shoulders, elbows, forearms, and wrists so that the ball can be returned quickly and accurately. For athletes aged 8–12 years, the development of hand-eye coordination is crucial as it forms the foundation for consistent and accurate technique. This study aims to analyze the effects of hand-eye coordination training using a circuit method on the backhand drive skills of table tennis athletes aged 8–12 years. The study employed a one-group pretest-posttest experimental design. Participants consisted of 20 table tennis athletes aged 8–12 years. The training program was conducted over four weeks at a frequency of three sessions per week. Each session included six coordination training stations performed in a circuit format. Backhand drive skills were measured through an accuracy test of 30 strokes using balls fed by a robot. Data were analyzed descriptively, followed by normality tests, homogeneity tests, and a paired-samples t-test at a significance level of 0.05. The analysis results showed a significant difference between the pretest and posttest scores for the backhand drive, with a p-value of 0.000. These results indicate an improvement in performance following the intervention. These findings suggest that hand-eye coordination training using the circuit method can improve players’ ability to track the ball, time their contact, and execute backhand strokes more consistently. Four weeks of hand-eye coordination training using the circuit method effectively improved the backhand drive skills of table tennis athletes aged 8–12 years. This program can serve as a structured, varied, and appropriate alternative to basic training for the development of young athletes.